2011
DOI: 10.2147/ijgm.s16413
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal pus in a hernia sac simulating strangulated femoral hernia: a case report

Abstract: Acute appendicitis involving the hernia sac is infrequent but well-documented in medical literature. In most instances, it occurs within the right inguinal (Amyand’s hernia) or right femoral hernia (de Garengeot hernia). The diagnosis is always mistaken for incarcerated groin hernia. During surgery, the appendix itself, either perforated or strangulated, is most commonly encountered within the hernia sac. In very rare occasions, only appendiceal pus is found in the hernia sac. In this paper, we report the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Diagnosis may be more difficult when patients present with abdominal pain alone ( n = 10) [39, 59]. A complete abdominal examination includes the inguinal region, thus, avoiding that the condition is not diagnosed until CT is performed [1], or when the patient’s condition has deteriorated [22, 80].…”
Section: Demographics and Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis may be more difficult when patients present with abdominal pain alone ( n = 10) [39, 59]. A complete abdominal examination includes the inguinal region, thus, avoiding that the condition is not diagnosed until CT is performed [1], or when the patient’s condition has deteriorated [22, 80].…”
Section: Demographics and Clinical Presentationmentioning
confidence: 99%
“…The most common hernia repair was through suture techniques ( n = 61), and with non-absorbable material (Table 5). The two most frequently specified methods were the McVay [29, 58, 80], Cooper ligament suture techniques [46, 61, 65], and the Lichtenstein repair [50]. Many authors refrained from the use a mesh when there was severe inflammation, perforation, or in the presence of an abscess [21, 48, 59].…”
Section: Demographics and Clinical Presentationmentioning
confidence: 99%
“…The tight neck of the femoral canal acts as a seal which limits inflammation and infection in the hernia sac; therefore perforation of the appendix in the hernia sac will rarely present with peritonitis. It has even been reported that, after the spontaneous reduction of a perforated appendix, the hernia neck seals off the infected collection, preventing peritoneal involvement [9]. …”
Section: Discussionmentioning
confidence: 99%